2019
DOI: 10.1007/978-3-030-32248-9_92
|View full text |Cite
|
Sign up to set email alerts
|

FocusNet: Imbalanced Large and Small Organ Segmentation with an End-to-End Deep Neural Network for Head and Neck CT Images

Abstract: In this paper, we propose an end-to-end deep neural network for solving the problem of imbalanced large and small organ segmentation in head and neck (HaN) CT images. To conduct radiotherapy planning for nasopharyngeal cancer, more than 10 organs-at-risk (normal organs) need to be precisely segmented in advance. However, the size ratio between large and small organs in the head could reach hundreds. Directly using such imbalanced organ annotations to train deep neural networks generally leads to inaccurate sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 13 publications
0
61
0
Order By: Relevance
“…On training a single multi-class model to segment all the structures of interest, it was observed that the imbalance in class labels due to large differences in OAR sizes led to poor performance on smaller structures. Augmenting the loss function based on class frequencies did not produce significant improvement, as previously observed in [18]. Consequently, three separate models were developed-one to segment the chewing structures and one each for the larynx and the constrictor muscle.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…On training a single multi-class model to segment all the structures of interest, it was observed that the imbalance in class labels due to large differences in OAR sizes led to poor performance on smaller structures. Augmenting the loss function based on class frequencies did not produce significant improvement, as previously observed in [18]. Consequently, three separate models were developed-one to segment the chewing structures and one each for the larynx and the constrictor muscle.…”
Section: Methodsmentioning
confidence: 75%
“…We compared the performance of our method with H&N OARs segmentation models from the published literature. These included state-of-the-art CNN models such as the 3D Unet [13], FocusNet [18], a H&N OAR-focused CNN [12], commercial atlas-based segmentation tool SPICE [5] and other atlas-based methods [24,25]. The mean DSCs for the different methods are summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…The quantitative and qualitative evaluation results( Wang et al [35] Zhu et al [24] Zhu et al [24] (with additional dataset) Gao et al [26] proposed As the quantitative and qualitative evaluation results illustrated in Table V and Fig. 5, we can observe that: (1) the segmentation accuracies achieved by are inferior than and , especially for very large OARs(TLs) and small OARs(ONs, and chiasm).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the compatibility of the proposed methods on very large and small OARS such as temporal lobe, pituitary, and chiasm was not considered. Gao, et al [26] proposed a FocusNet to balance large and small OARs segmentation. It achieved more accurate segmentation on small OARs with training OAR specific model, which is timeconsuming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation